Comparative study of nitrogen release from compound fertilizers in silty loam and sandy loam soils - J. Preesong; P. Phromnak; F. Paenklang; V. Thammanatsakun; Sukunya Yampracha (International Journal of Agricultural Technology, 2025)
Most Thai farmers cultivate field crops on coarse-textured soils that are inherently low in fertility and highly susceptible to nutrient leaching, resulting in low nitrogen use efficiency. The results indicated that the Hin Kong (Hk) soil series exhibited greater ammonium-N and urea-N release than the Chanthuk (Cu) soil series, reaching 624 and 54.4 mg N kg⁻¹, respectively. In contrast, the Cu soil series showed higher nitrate-N release, with 364 mg N kg⁻¹. Among the fertilizer formulations, 15-7-18 produced the highest ammonium-N, urea-N, and available nitrogen release, although these values were not significantly different from those of the 15-5-20 formulation. Conversely, the 15-5-20 formulation generated the highest nitrate-N release (536 mg N kg⁻¹), but its ammonium-N and available N release remained statistically comparable to the 15-7-18 formulation. The 15-7-18 fertilizer consistently promoted early-stage ammonium accumulation, reflecting its relatively ammonium-based composition, whereas the 15-5-20 formulation favoured rapid nitrate build-up in the Cu soil. The 16-8-8 formulation exhibited a more gradual release pattern in both soils, maintaining available N at later stages and suggesting slower transformation and solubilization rates compared with the other formulations. These findings indicate that nitrogen release dynamics are jointly governed by fertilizer formulation and soil properties—including not only soil texture but also organic matter content, cation exchange capacity, and soil acidity. Temporal patterns further revealed an initial rapid nitrogen release followed by stabilization, reflecting the combined effects of soil physical structure, chemical characteristics, microbial activity, and fertilizer traits. Selecting an appropriate fertilizer formulation is therefore essential for improving nitrogen use efficiency in coarse-textured soils.
Keywords: Soil Carbon and Nitrogen Dynamics; Soil Management and Crop Yield; Rice Cultivation and Yield Improvement